Los gatos black on Halloween - Montes, Marisa (Henry Holt and Company, 2006)
Easy to read, rhyming text about Halloween night incorporates Spanish words, from las brujas riding their broomsticks to los monstruos whose monstrous ball is interrupted by a true horror.